2018
DOI: 10.1103/physrevd.97.064042
|View full text |Cite
|
Sign up to set email alerts
|

Extended I-Love relations for slowly rotating neutron stars

Abstract: Observations of gravitational waves from inspiralling neutron star binaries-such as GW170817can be used to constrain the nuclear equation of state by placing bounds on stellar tidal deformability. For slowly rotating neutron stars, the response to a weak quadrupolar tidal field is characterized by four internal-structure-dependent constants called "Love numbers". The tidal Love numbers k el 2 and k mag 2 measure the tides raised by the gravitoelectric and gravitomagnetic components of the applied field, and th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(56 citation statements)
references
References 70 publications
(286 reference statements)
3
50
1
Order By: Relevance
“…Our results agree with those of Ref. [37] and with the revised ones in Ref. [44] in the relevant regimes [71].…”
Section: A Relevance Of the Magnetic Tlnssupporting
confidence: 93%
See 1 more Smart Citation
“…Our results agree with those of Ref. [37] and with the revised ones in Ref. [44] in the relevant regimes [71].…”
Section: A Relevance Of the Magnetic Tlnssupporting
confidence: 93%
“…However, there exist some approximate EoSindependent relations, Σ i = Σ i (Λ i ), that connect the magnetic TLNs to the standard electric TLNs [44]. Notice that the magnetic TLNs depend on the properties of the fluid [34,37,70]. In particular, the magnetic TLNs for irrotational fluids or for static fluids have the opposite sign and the quasiuniversal relation also depends on the fluid properties.…”
Section: A Relevance Of the Magnetic Tlnsmentioning
confidence: 99%
“…In particular, the static and irrotational magnetic TLNs satisfy two different approximately-universal relations, as discussed in Refs. [18,20], where some fits for such relations are pro-vided in both cases.…”
Section: Discussionmentioning
confidence: 97%
“…Meanwhile, in 2013 Yagi [21] used the result of DN to compute the effect of the magnetic TLNs in the waveform and to compute some quasi-universal relations [27,28] among TLNs of different parity and different multipole moments. In 2015, Landry and Poisson (hereafter, LP) discovered [3] that the magnetic TLNs depend on the properties of the fluid (see also [20,29]). In particular, they found that the magnetic TLNs for irrotational fluids or for static fluids are different and have the opposite sign.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation